Seed Mucilage: Biological Functions and Potential Applications in Biotechnology - Tsai, Allen Yi-Lun; McGee, Robert; Dean, Gillian H; Haughn, George W; Sawa, Shinichiro (Plant and cell physiology, 2021)
Abstract In plants, the diaspore (seed dispersal unit) may include a seed coat and/or pericarp to protect the embryo and assist in dispersion. In many species, the seed coat and/or pericarp secrete a gelatinous mixture of cell wall polysaccharides known as mucilage. In several species, mucilage synthesis, secretion and modification have been studied extensively as model systems for the investigation of plant cell wall structure and function. Despite this, efforts toward understanding the role of mucilage have received less attention. Mucilage has been hypothesized to impact seed dispersal through interaction with soil, protecting the seed in the gut following ingestion by animals or affecting the ability of seeds to sink or float in water. Mucilage has been found to influence seed germination and seedling establishment, most often during abiotic stress, probably by maintaining seed hydration when water is scarce. Finally, mucilage has been documented to mediate interactions with various organisms. Advances in transgenic technology should enable the genetic modification of mucilage structure and function in crop plants. Cells synthesizing mucilage may also be a suitable platform for creating custom polysaccharides or proteins with industrial applications. Thus, in the near future, it is likely that research on seed mucilage will expand well beyond the current focus. Here we summarize our understanding of the biological functions of mucilage and provide an outlook on the future of mucilage research.